PERENCANAAN KONSEPTUAL IMPLEMENTASI MULTIPLE INTELLIGENCES RESEARCH UNTUK MENINGKATKAN NILAI-NILAI KARAKTER SOSIAL DAN RELIGIUS SISWA PADA PEMBELAJARAN IPS DI SD PLUS AL-KAUTSAR KOTA MALANG DAN SD MUHAMMADIYAH 09 PANGLIMA SUDIRMAN MALANG - Siti Nurjanah; Zenudin Muhammad; Alfiana Yuli Efiyanti (Inspiratif Pendidikan, 2023)
Multiple Intelligences Research (MIR) was born from the premise of MI which was coined by Gardner. The results of MIR play an important role in the application of MI learning process, the benefits of MIR for students, teachers, parents and schools can be used to determine student learning styles, the tendency of intelligence possessed by each child shows how the child’s learning style is. With the use of MIR, it can be easily divided into classes (class mapping), the results of this MIR can be used as a school guide to divide classes. So far, most of the class division guidelines are based on cognitive value rankings or alphabetical order. The purpose of this study was to analyze how the conceptual planning of Multiple Intelligences Research on class grouping in social studies learning to increase the values ​​of social and religious characters in SD Plus Al-Kautsar and SD Mudammadiyyah 9 Panglima Sudirman Malang. Data was collected by observing students, interviewing teachers, school principals and filling out Google from and documentation. This study has indicators that are used as guidelines for planning Multiple Intelligences Research as a test tool in grouping students to facilitate the learning process in the classroom. That way we can find out how to increase social and religious values ​​in students during the social studies learning process through Multiple Intelligences Research. The results of this study are expected to be applied by elementary school teachers to make the learning process easier through Multiple Intelligences Research as a class grouping to make it easier to choose methods, media and student learning styles.